テイシュウハ パルス サウンダー ニヨル カブ デンリソウ カンソク ノ キソ ジッケン - 宮崎, 茂; ミヤザキ, シゲル; MIYAZAKI, Shigeru (国立極地研究所, 1974)
P(論文) In order to obtain basic data on the lower ionosphere in the Antarctic region, the usual ionosonde was remodeled into a portable type of low-frequency pulse sounder equipped with all solid state circuits except the final stages, which was suitable to field experiment. Three experiments were carried out. The first experiment was carried out at point F16 in the Antarctic Continent about 20km apart from Syowa Station by using a couple of doublet antennas on the snow surface and the total length of each antenna was 475 m. The second experiment was carried out at Skjegget Peak, Skarvs Nes about 50 km apart from Syowa Station by using a couple of 360 m high vertical delta antennas terminated by 600 ohms and the length of each element was 500 m. The third experiment was carried out at point F18 near F16 in the Antarctic Continent by using a couple of doublet antennas on the snow surface and the total lengths of the antennas were 1600m and 1000m. In the experiments reflected echoes from the lower ionosphere were observed clearly, and time variations of the lower ionosphere in quiet and disturbed conditions were also observed with a comparatively low power (less than 1 Kw) by using a couple of doublet antennas which lay on the snow surface. departmental bulletin paper